Education Policy Making Pattern "with an Approach" - Pikson Lenggetio; F.J.A Oentoe; Orbanus Naharia; Benny B. Binilang (International Journal of Education, Information Technology, and Others, 2020)
This study aims to determine the pattern of education policy making at district/city education offices in North Sulawesi province, by reviewing the problems in education policy analysis procedures, education policy implementation procedures, monitoring and evaluation procedures for education policies, as well as education policy follow-up procedures carried out in three (3). 3) research locus, namely the Manado City Education and Culture Office, the Bitung City Education and Culture Office and the North Minahasa Regency Education and Culture Office. North Sulawesi Province. The data collection technique is done through observation, interview and documentation study. The data analysis technique is the analysis in cases and cross cases. The entire data obtained that has been collected will be processed according to each case and then grouped based on location characteristics. The findings of this study are that in the past before the reform era or in the New Order era, the parties involved in the formulation of education policy were only at an internal order, not involving external or external parties, now in the era of reform and regional autonomy in determining policies including education policy all existing procedures must be involved including external parties. In each of the existing education offices, they do not follow the standard procedures or mechanisms set out in the regulations but many have been bypassed. Then the conclusion of this study is 1). All procedures are determined by the availability of existing human resources. 2). The procedures so far have not followed the existing and standardized mechanisms, 3). procedures in all existing education offices are the same according to regulations, 4). however, it has different characteristics, namely the characteristics possessed by each region are different so that the content of policies and results so far have also varied, including the quality and quantity of the policy itself.